A Framework for Facilitating Experiential Learning. (December 2015) - Matsuo, Makoto
Although learning from experience is recognized as important for the development of managers, there is no systematic model regarding how to facilitate experiential learning. This study was designed to develop a theoretical framework for the ability to learn from experience. Drawing on the literature, I have developed a model in which five facilitators (seeking challenging tasks, critical reflection, enjoyment of work, learning goal orientation, and developmental network) directly and indirectly facilitate performance of the four steps of Kolb's experiential learning process. The central contribution of this study is to propose a framework that integrates factors that facilitate experiential learning in various fields. The present research compensates for the shortcomings of Kolb's experiential learning cycle.